2022
DOI: 10.1186/s12991-022-00417-y
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cognitive behavior therapy on anxiety and depression during COVID-19 pandemic: a systematic review and meta-analysis

Abstract: Background The global spread of coronavirus has caused many physical and mental health problems throughout the world. Depression and anxiety are among the issues that people are experiencing abundantly, along with other mental health disorders, during this period. Cognitive behavior therapy (CBT) is one of the approaches that is effective on improving most of the psychological issues including depression and anxiety. The objective of this systematic review and meta-analysis was to assess the ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…There is an overall agreement in most of the studies that a single dose of 10 mg/kg fenofibrate combined with conventional phototherapy has a significant effect on lowering TSB in a shorter time compared with phototherapy alone [8,17,[19][20][21][22][23]. In contrast, the research that Prabha and Saravanan [27] conducted found no statistically significant differences in the bilirubin reduction rate with a single dosage of fenofibrate (10 mg/kg) after 48 h in the intervention group.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…There is an overall agreement in most of the studies that a single dose of 10 mg/kg fenofibrate combined with conventional phototherapy has a significant effect on lowering TSB in a shorter time compared with phototherapy alone [8,17,[19][20][21][22][23]. In contrast, the research that Prabha and Saravanan [27] conducted found no statistically significant differences in the bilirubin reduction rate with a single dosage of fenofibrate (10 mg/kg) after 48 h in the intervention group.…”
Section: Discussionmentioning
confidence: 90%
“…On the other hand, many studies examined the use of fenofibrate in the treatment of neonatal hyperbilirubinemia and demonstrated its usefulness. Oral administration of fenofibrate as a single dose of 10 mg/kg combined with phototherapy could reduce the total serum bilirubin (TSB) and the duration of hospitalization [8,[17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Studies were carried out to understand depression in a multidimensional way (Adabla & Nabors, 2022; Davey & Harrison, 2022;de Castro et al, 2023;Kasa et al, 2022;Kim et al, 2022;Zamiri-Miandoab et al, 2022). These studies included many constructs such as the causes and consequences of depression, comorbidity status.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…However, the meta-analysis did not show a separated effect of fenofibrate, independent of phototherapy, on reducing the bilirubin levels. Thus, the authors recommended further studies [99]. In a recent study, authors reported that combining conventional phototherapy with a single oral dose of 10 mg/kg fenofibrate may shorten the time it takes to lower the bilirubin levels.…”
Section: Fibratementioning
confidence: 99%